THE EFFECT OF ASSEMBLR EDU INTEGRATED INTO THE PROBLEM-BASED LEARNING MODEL ON STUDENTS’ MOTIVATION AND LEARNING OUTCOMES IN REACTION RATE MATERIAL AT SMAN 1 GOWA - Feby Stefania Baan Tasik; Muhammad Syahrir; Muhammad Anwar (JCER (Journal of Chemistry Education Research), 2026)
This study employed a quasi-experimental approach to investigate how the integration of augmented reality (AR) technology, specifically Assemblr Edu, within a Problem-Based Learning (PBL) model influenced the motivation and learning outcomes of eleventh-grade students at SMA Negeri 1 Gowa, with a focus on reaction rate as the subject matter. A post-test only control group design was adopted as the methodological framework. The findings demonstrated that students in the experimental group outperformed their counterparts in the control group across both measured variables. In terms of learning motivation, the experimental group recorded a mean score of 80.61, compared to 73.94 in the control group. Regarding academic achievement, the experimental group similarly obtained a higher mean score of 82.91, while the control group attained 75.69. Statistical analysis was conducted through inferential methods, employing the independent samples t-test and the Mann-Whitney test where appropriate. For learning motivation, the calculated t-value (3.33) exceeded the critical t-value (1.67), indicating a statistically significant difference. Likewise, for learning outcomes, the obtained Z-value (1.99) surpassed the critical Z-value (1.64), confirming significance. These results collectively suggest that the incorporation of Assemblr Edu AR-based media within a PBL model exerts a meaningful and statistically significant influence on both the motivational engagement and academic performance of students in reaction rate instruction.